PENGARUH NON PERFORMING LOAN DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP RETURN ON ASSETS PADA PD. BKK CABANG LARANGAN DI KABUPATEN BREBES - Sri Rahayu (Jurnal Strategik, 2019)
Abstract This study is entitled "The Effect of Non-Performing Loans and Operating Costs Operating Income on Return On Assets in PD. BKK Prohibition Branch in Brebes Regency ". The research method used is a case study on PD. BKK Larangan Branch in Brebes Regency, while the data collection methods used were survey, interview and library research. In testing hypotheses using financial ratio tools, the classic assumption test and analysis of multiple regression coefficients with, t and F and the coefficient of determination. Hypothesis testing with t test (partial test) for the Non Performing Loan variable the number of Return On Assets significance of 0.684 is greater than 0.05 means that the Non Performing Loan does not significantly influence partially on Return On Assets on PD. BKK Prohibition Branch in Brebes Regency. Hypothesis testing with partial test for Variable Operational Costs Operating Income Return on Assets significance value of 0.105 is greater than 0.05 means that Operational Costs Operating Income is not significant partial effect on Return On Assets on PD. BKK Larangan Branch in Brebes Regency. And simultaneous hypothesis testing Non Performing Loan variables and Operational Cost of Operating Income on Return On Assets significance number 0.122 is greater than 0.05 means that the Non Performing Loan variable and Operational Cost of Operating Income have no significant effect simultaneously on Return On Assets on PD BKK. Prohibition Branch in Brebes Regency.